Pengendalian Persediaan Bahan Baku Bawang Merah Untuk Produksi Bawang Goreng Dengan Metode Economic Order Quantity (EOQ) Dan Just In Time (JIT) - Nur Muflihah, Minto, Muhammad Farras Jayayudha Satria, Andhika Mayasari, (Journal of Industrial Engineering and Technology, 2024)
Effective planning to manage the procurement of raw materials is crucial for maintaining productivity in production activities and controlling costs. Indonesian enterprise UD. XYZ is dedicated to the manufacturing of fried onions. However, between April 2022 and June 2023, there have been regular fluctuations in the raw material availability for the production process, which has resulted in subpar output levels and unmet demand. To solve this problem, this study will use time series forecasting techniques to estimate the demand for fried onions and the Economic Order Quantity method to control raw material supply. Furthermore, this study uses the Just In Time approach to determine the minimum inventory cost. Both systems are anticipated to lessen the effects of changes in raw material availability. Based on the research results, the linear regression method was used for forecasting, which predicted an average demand of 1354 Kg of fried onions with a MAPE value of 2,79%, MAD 27,59, and MSD 1317,81. Then, an EOQ value of 1992,85 kg was calculated using the Economic Order Quantity (EOQ) and Just In Time (JIT) methods. This resulted in a total minimum storage cost of Rp. 2.989.271.